Serological evidence of arboviruses and coccidia infecting horses in the Amazonian region of Brazil - Gomes, Fabio Alves; Jansen, Ana Maria; Machado, Rosangela Zacarias [UNESP]; Jesus Pena, Hilda Fatima; Fumagalli, Marcilio Jorge; Silva, Angelica; Alves, Bruna Farias; Rodrigues Roque, Andre Luiz; Moraes Figueiredo, Luiz Tadeu (Public Library Science, 2019)
Background Arboviruses and protozoans can cause neurologic disorders in horses. In Brazilian Amazon, several horses presenting signs compatible with disorders caused by these infectious agents have been observed. Objective To contribute to the knowledge of this epidemiological picture, we sought to construct a serological diagnostic panel for neurotrophic infectious agents in local horses. Material and methods A total of 213 blood samples from horses were collected from 29 farms in three municipalities. Samples were evaluated and considered positive when they met the following criteria: titers >= 1:80 with the indirect fluorescent antibody test (IFAT) for apicomplexan protozoans; positive recombinant enzyme-linked immunosorbent assay (ELISA) with subsequent titers >= 1:10 by the PRNt for viruses; and detection under direct microscopic examination for Trypanosoma evansi. Results No horses were found to be infected by T. evansi, and only two were infected Toxoplasma gondii and/or Neospora spp. The highest protozoan infection rate was observed for Sarcocystis neurona (40.3%; n = 86/213). Among the positive ELISA samples tested by the plaque reduction neutralization test (PRNT90), 92% (n = 76/83) were positive for St Louis Encephalitis virus, 43% (n = 6/14) were positive for West Nile virus and 33% (n = 16/48) were positive for Mayaro virus. Eighteen percent (n = 39/213) of horses were co-infected by S. neurona and at least one arbovirus, particularly SLEV and/or MAYV. Conclusion Samples positive for SLEV associated with S. neurona, including samples from horses that had recovered from neurological signs were frequent, and must be considered when investigating the possible causes of neurological diseases in South Roraima horses.